PENERAPAN PEMBERIAN EKSTRAK DAUN PEPAYA SEBAGAI PENGEMPUK DAGING PADA AYAM JOPER - Sriyani, N.L.P.; Dewi, G.A.M.K.; Ariana, I.N.T.; Suarta, G. (Buletin Udayana Mengabdi; Vol 23 No 5 (2024): Buletin Udayana MengabdiDO - 10.24843/BUM.2024.v23.i05.p09, 2023)
Super native chicken (Joper) is the result of a cross breed between native chicken with layer. Joper is seen in the ability to produce meat, especially in the breast and thigh organs, like broilers. However Joper has a low quality of meat tenderness. Papaya leaves are often used as meat tenderizers because they contain the enzyme papain. Papaya leaves are used in livestock as feed or mixed in drinking water in the form of papaya leaf juice. Abiasemal Village many Joper chicken farmers, both independent farmer or grup.Farmers have several obstacles in the development of Joper chicken where the results of meat that have low tenderness are obtained. This program will try to socialize the implementation of papaya leaf juice as meat tenderizer for Joper chicken in the village. The result of this program is the participation of the member group farmers is the good. Papaya leaf extract application in drinking water has been implemented by group farmer produce meat with increased tenderness with a not bitter taste, and one of the group members is interested to produce papaya leaf exstract to be sold in other group members. Keywords: papaya leaves, joper chicken, tenderness of meat